2014
DOI: 10.1186/1475-2891-13-31
|View full text |Cite|
|
Sign up to set email alerts
|

U.S. adults are not meeting recommended levels for fish and omega-3 fatty acid intake: results of an analysis using observational data from NHANES 2003–2008

Abstract: BackgroundThe American Heart Association’s Strategic Impact Goal Through 2020 and Beyond recommends ≥ two 3.5-oz fish servings per week (preferably oily fish) partly to increase intake of omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). We examined the intake of total fish, fish high in omega-3 fatty acids, α-linolenic acid, EPA, and DHA in U.S. adults (19 + years) using data from the National Health and Nutrition Examination Survey, 2003–2008.MethodsUsual intakes from foods alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
170
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(180 citation statements)
references
References 17 publications
6
170
2
2
Order By: Relevance
“…Comparison between individual developed countries shows that average intake of ALA among adults has about a 3-fold variation [29,43,44] (Table 1). For example, French adults consume an average of about 0.8 g/d ALA, which is about one half to one third of the average intake of adults in Belgium, The Netherlands, Denmark, Finland and Germany ( Table 1).…”
mentioning
confidence: 99%
“…Comparison between individual developed countries shows that average intake of ALA among adults has about a 3-fold variation [29,43,44] (Table 1). For example, French adults consume an average of about 0.8 g/d ALA, which is about one half to one third of the average intake of adults in Belgium, The Netherlands, Denmark, Finland and Germany ( Table 1).…”
mentioning
confidence: 99%
“…Rates of depression vary widely across the world [50] and the intake of long chain omega 3 varies between countries [51], with several including Australia [52] and the USA [53] reporting that population intakes are below the recommended levels. A recent study in the USA examined plasma LCn3PUFA concentrations as a biomarker assessment of LCn3PUFA status in a nationally representative cohort (NHANES) and reported that nearly the whole population had levels below those associated with cardiovascular protection [54].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these recommendations, the intake of marine omega-3 fatty acids is low among the average U.S. adult population (41 mg/day and 72 mg/day of EPA and DHA from foods and supplements, respectively) [26] . Whether the aforementioned dietary recommendation or other doses of marine omega-3 fatty acids are suitable for OSA patients at high risk of CVD and with suboptimal marine omega-3 intake remains to be established.…”
Section: Resultsmentioning
confidence: 99%